Brilliant angle-independent structural colours preserved in weevil scales from the Swiss Pleistocene. (29th April 2020) - McDonald, Luke T.; Narayanan, Suresh; Sandy, Alec; Saranathan, Vinodkumar; McNamara, Maria E.
Abstract : Extant weevils exhibit a remarkable colour palette that ranges from muted monochromatic tones to rainbow-like iridescence, with the most vibrant colours produced by three-dimensional photonic nanostructures housed within cuticular scales. Although the optical properties of these nanostructures are well understood, their evolutionary history is not fully resolved, in part due to a poor knowledge of their fossil record. Here, we report three-dimensional photonic nanostructures preserved in brightly coloured scales of two weevils, belonging to the genus Phyllobius or Polydrusus, from the Pleistocene (16–10 ka) of Switzerland. The scales display vibrant blue, green and yellow hues that resemble those of extant Phyllobius/Polydrusus . Scanning electron microscopy and small-angle X-ray scattering analyses reveal that the subfossil scales possess a single-diamond photonic crystal nanostructure. In extant Phyllobius/Polydrusus, the near-angle-independent blue and green hues function primarily in crypsis. The preservation of far-field, angle-independent structural colours in the Swiss subfossil weevils and their likely function in substrate matching confirm the importance of investigating fossil and subfossil photonic nanostructures to understand the evolutionary origins and diversification of colours and associated behaviours (e.g. crypsis) in insects.